Metal-antimicrobial peptides combo: promising weapons to combat bacteria invaders - Lucia Falcigno; Simone Braccia; Rosa Bellavita; Gabriella D'Auria; Annarita Falanga; Stefania Galdiero (Frontiers Media S.A., 2024)
Antimicrobial resistance has significantly increased over the last 30 years, prompting scientists to continuously look for novel, effective ways to combat drug-resistant bacteria and fungi. Due to their broad range of effectiveness, ease of synthesis, and ability to avoid resistance, antimicrobial peptides (AMPs) represent a potential approach. The direct investigation of metal effects on peptide activity has not received much attention. Divalent metal ions such as Zn(II), Cu(II), Ni(II), and Fe(II) do, in fact, influence some AMPs, producing an effect on their mode of action or function. Although the precise process by which metals are involved in microbial death is not well understood, this review goes into detail on several potential strategies to enhance AMPs activity through the synergy with metals. Important variables in these interactions include the individual peptide sequence, the type of metal ion, the capacity of metal to form chelates, and the softness of the ligand/metal complex. This article offers a thorough summary of the ways in which metal ions alter the structure of AMPs to boost their activity or sequester metal to impact on bacteria function.